Snakebite in Bangladesh: Public Health Challenges and Awareness Initiatives - Sarkar, Santana Rani; Ray, Nitai Chandra (Community Based Medical Journal, 2025)
Snakebite envenoming presents a significant public health challenge in Bangladesh, particularly affecting rural and underserved populations. Infections resulting from snakebites compound medical complications, leading to increased morbidity and mortality. In this article, focuses on the complex public health challenges associated with snakebite infections in Bangladesh and emphasize the importance of awareness initiatives. Snakebites often occur in remote areas with limited access to medical care, resulting in delayed treatment and an increased risk of infections at the bite site. Secondary infections, caused by various pathogens introduced by the snake's fangs or subsequent wound contamination, further worsen the health burden. Common bacterial pathogens include Staphylococcus spp., Streptococcus spp., and various Gram-negative bacteria, which can lead to severe systemic infections if not promptly and adequately treated. The challenges in addressing snakebite infections are exacerbated by a lack of healthcare infrastructure, limited availability of antivenoms, and insufficient training among healthcare providers. Additionally, socio-economic factors and cultural beliefs often result in a reliance on traditional healers, delaying effective medical intervention. To tackle these issues, public health initiatives must prioritize increasing community awareness about the dangers of snakebites and the importance of timely medical treatment. Educational campaigns should target the general population and healthcare workers, emphasizing first-aid measures, the need for rapid hospital referral, and proper wound care to prevent infections. Strengthening healthcare systems, ensuring the availability of antivenoms, and conducting epidemiological research, and increasing awareness and implementing targeted interventions are crucial steps toward mitigating the impact of snakebite infections. CBMJ 2025 July: vol. 14 no. 02 P:201-207